2021
DOI: 10.1038/s41431-021-00923-9
|View full text |Cite
|
Sign up to set email alerts
|

Couples’ experiences with expanded carrier screening: evaluation of a university hospital screening offer

Abstract: Preconception carrier screening offers couples the possibility to receive information about the risk of having a child with a recessive disorder. Since 2016, an expanded carrier screening (ECS) test for 50 severe autosomal recessive disorders has been available at Amsterdam Medical Center, a Dutch university hospital. This mixed-methods study evaluated the experiences of couples that participated in the carrier screening offer, including high-risk participants, as well as participants with a general population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 41 publications
5
37
0
Order By: Relevance
“…Another example to support our argument would be the ability to prepare in advance for the possibility of having a child with a hereditary condition. Within our study sample, up to 75% of participants agreed they would accept RGCS because of this reason while other studies (van Dijke et al., 2021; Nijmeijer et al., 2019; Plantinga et al., 2016; Propst et al., 2018; Schuurmans et al., 2020) – with a different way of questioning – reported that this reason was not often chosen by study participants (2%–33%). Compared with earlier studies, our findings also show a larger share of participants who would elect RGCS to prevent the birth of an affected child or because of the fear of regret afterwards.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Another example to support our argument would be the ability to prepare in advance for the possibility of having a child with a hereditary condition. Within our study sample, up to 75% of participants agreed they would accept RGCS because of this reason while other studies (van Dijke et al., 2021; Nijmeijer et al., 2019; Plantinga et al., 2016; Propst et al., 2018; Schuurmans et al., 2020) – with a different way of questioning – reported that this reason was not often chosen by study participants (2%–33%). Compared with earlier studies, our findings also show a larger share of participants who would elect RGCS to prevent the birth of an affected child or because of the fear of regret afterwards.…”
Section: Discussionmentioning
confidence: 67%
“…(2018), van Dijke et al. (2021), and Nijmeijer et al. (2019) only very few participants (3%–15%) selected this reason in favor of RGCS.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Successful niche developments need scaling up to gradually expand. The two currently available ECS initiatives in the Netherlands can serve as examples of a learning phase and evaluation might provide key insights to consider for potentially scaling up implementation [ 35 , 36 ]. It was expected by professionals in this study that the use of ECS will increase in the future, although currently carrier screening is not widely available and public awareness is low [ 37 ].…”
Section: Discussionmentioning
confidence: 99%